2019
DOI: 10.1002/ar.24098
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Large Animal Model for Eustachian Tube Functional Study in Miniature Pigs

Abstract: This study was performed to investigate whether miniature pigs are a suitable animal model for studies of the Eustachian tube (ET). Sixteen Chinese experimental miniature pigs were used in this investigation. Ten animals were used for anatomical and morphometric analyses to obtain qualitative and quantitative information regarding the ET. Three animals were used for histological analysis to determine the fine structure of ET cross‐sections. Three animals were used to investigate the feasibility of balloon dila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“… An et al. (2019) obtained qualitative and quantitative information on the eustachian tube (ET) by studying 16 domestic small experimental pigs and measuring their eustachian tube structures.…”
Section: Resultsmentioning
confidence: 99%
“… An et al. (2019) obtained qualitative and quantitative information on the eustachian tube (ET) by studying 16 domestic small experimental pigs and measuring their eustachian tube structures.…”
Section: Resultsmentioning
confidence: 99%
“…Our study investigated the overall shape and dimensions of the porcine ET using the porcine ET phantom. A previous study reported the average total length of the ET as 24.2 mm using a cadaveric miniature porcine ET model 21 . This was close to the average length of the porcine ET phantom (23.18 mm) observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The technical feasibility of stent placement in a porcine ET was assessed by fluoroscopic and endoscopic images obtained during the procedure and computed tomography (CT) afterward. The stent sizes were selected according to the diameter (2.3 to 3.4 mm) and length (24.2 to 36.4 mm) of the normal ET in a porcine model [15,16]. This study was approved by the Institutional Animal Care and Use Committee of the Asan Institute for Life Sciences (2020-12-189) and conformed to US National Institutes of Health guidelines for humane handling of laboratory animals.…”
Section: Methodsmentioning
confidence: 99%